Water for life: natural resource and essential human rights to sustainable development - Machado, Clara; Ribeiro Oliveira, Rayza (Revista de Direito da Cidade, 2020)
The alarming and increasing scarcity of drinking water on the planet adds a new paradigm in the international legal scene, in order to protect human life and ensure the promotion of quality of life for present and future generations as a form of sustainable development, that is, the paradigm of the human right to water. Thus, this article aims to present, through the evolution of the environmental theme in the international scenario, in view of the consideration of water as an objective of sustainable development in the UN 2030 Agenda, the new conception of the right to water, from the recognition of the right to the healthy environment, both being human rights, essential to the quality of life and the dignity of human life. Finally, to conclude that, although the right to water is not yet recognized as a human right in the Brazilian legal system, there is a growing mobilization in this regard in the national scenario. The methodology used was based on a qualitative approach to the problem, being a research of exploratory nature, using the methodological procedure of bibliographical and documentary research, through the analysis of doctrines, documents, legislation and other scientific texts related to the subject.